Whole-plant forage, grain, or nonheading sorghum silages for growing cattle - R. Smith; K. Bolsen; H. Ilg; J. Hoover; J. Dickerson (Kansas Agricultural Experiment Station Research Reports, 1985)
Three sorghum hybrid types were used to make six silages in the fall of 1983. Eight silage rations were compared using 160 steer calves in an 84-day growing trial. Using forage sorghum silage as a base (100), grain sorghum silage had a feeding value of 133, and nonheading sorghum silage 89, when evaluated for comparative rates and efficiencies of gain. Silages from concrete stave silos produced faster and more efficient steer gains than silages from Silopress® bags. Rolling the grain sorghum silages at feeding time to break 95% of the grain significantly improved steer performance. The feeding value of corn silage was not enhanced by processing.
Keywords: Cattlemen' s Day; 1985; Kansas Agricultural Experiment Station contribution; no. 85-319-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 470; Beef; Forage; Grain; Sorghum silage; Growing cattle